К эволюции поэтического идиолекта А. Межирова - Шульскaя О. (Kalbotyra, 1970)
In this article an attempt is made to solve diachronic problems in the linguistic description of the language of the poet. A comparative analysis is made of two stages in the development of A. Mezhirov’s poetry based on two selections of the poet’s work – ‘Vetrovoje steklo’ and ‘Proshanije so Snegom’. From the vocabulary of these works frequency lists were compiled of nouns adjectives and verbs. The data obtained was used in an analysis of semantic groups in the poet’s vocabulary. The comparative analysis of these selections carried out by the method of structural poetics enables us to come to a conclusion on the evolution of Mezhirov’s work over a short space of time.